Dietary nitrate improves cognitive function and exercise performance during prolonged intermittent sprint cycling - Thompson, C.; Wylie, L. J.; Fulford, J.; Jeukendrup, A. E.; Vanhatalo, A.; Jones, A. M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Dietary nitrate (NO3-) supplementation has been shown to improve intermittent exercise performance of short duration (~15-20 min; Wylie et al. 2013, Bond et al. 2013). However, success in team sport is determined not only by the ability to maintain high-intensity intermittent exercise, but also by the speed and accuracy of decision making. Dietary NO3-, which may enhance nitric oxide bioavailability, has the potential to improve both physical and cognitive performance via its influence on blood flow and muscle energetics. Therefore, the aim of this study was to assess the effects of NO3- on performance and cognitive function during an extended intermittent sprint protocol. Methods: Following ethical approval, 16 male amateur team sport players were familiarised to the intermittent sprint test (IST) (two 40-min "halves" of repeated 2-min blocks consisting of a 6-s "all-out" sprint, 100-s active recovery at 35% VO2max and 20 s of rest), during which cognitive tasks were simultaneously performed. In a double-blind randomised crossover design, subjects were allocated to receive NO3--rich (BR; 140 mL./d; 12.8 mmol of NO3-,) and NO3--depleted (PL; 140 mL/d; 0.08 mmol NO3-) beetroot juice for 7 days (Beet It, James White Drinks Ltd., U.K). On day 7 of supplementation, subjects completed the full IST. Results: There was a significant interaction effect (supplement by sprint number) on total work done during the 1st (BR: 61.2±19.1 vs. PL: 58.1±17.1 kJ; P<0.05), but not the 2nd, half of the IST. Specifically, subjects completed more work in 5 of 20 1st half 6-s sprints in BR compared to PL (P<0.05). Reaction time of response to the cognitive tasks in the 2nd half of the IST was improved in BR compared to PL (P<0.05) (BR 1st: 826±100 vs. 2nd: 825±96 ms; PL 1st: 824±114 vs. 2nd: 847±118 ms). However, there was no difference in response accuracy (BR 1st: 6.9±6.1 vs. 2nd: 7.1±7.3; PL 1st: 7.3±6.0 vs. 2nd: 7.1±5.8 incorrect responses; P>0.05). Discussion: In conclusion, dietary NO3- supplementation improved total work done and sprint performance during the 1st 40 min of the IST. Moreover, reaction time during the cognitive tasks was improved with NO3- in the 2nd compared to the 1st half. These findings suggest that dietary NO3- enhances repeated sprint performance and may attenuate the decline in cognitive function that typically occurs during team sport gameplay.